Penguatan Literasi Membaca melalui Program Pojok literasi Sekolah dalam PLP2 Terintegrasi KKN Pendidikan - Jannah, Miftahul; Febrianti, Febi; Maulana, Saeful; Maharani, Marlin; Novita, Novita; Oktafia, Emilia; Karzai, Ismadaniel; Ramzin, Ramzin; Ilmiawan, Ilmiawan (LPPM UMRI, 2025)
This community service activity was motivated by the low reading literacy culture at Madrasah Aliyah NW Suwangi, as evidenced by the lack of reading facilities and the absence of regular reading activities. A literacy corner is considered an effective approach to increase reading interest if implemented in a participatory manner. This activity applies a collaborative-participatory approach based on service learning in the context of Participatory Action Research (PAR), involving PLP2/KKN students as facilitators, teachers as supporters, and students as the main focus. Information was collected through participatory observation, semi-structured interviews, focus group discussions (FGD), and documentation, then analyzed using descriptive qualitative methods. The data showed a significant increase in students' reading literacy, as evidenced by increased visits to the literacy corner, reading time, and active participation in literacy discussions. Thus, the literacy corner program in the context of PLP2 integrated with KKN Education has proven successful in improving literacy culture in secondary schools, although the sustainability of the program requires strengthening cooperation between teachers, students, and the school.